The contribution of smallholders' livelihood activities on income inequality and poverty: Case study from rural Tanzania - Gregor Mager; Anja Faße (Journal of International Development, 2023)
This study uses a unique panel dataset on micro data with 786 households over 3~years (2014, 2016 and 2018) at the community level in Tanzania, assessing the contribution of different income sources on the changes in income inequality and poverty. The results show that in contrast to other income sources, non-farm self-employment is the only source with a constant poverty-decreasing effect. The inconsistency of the different income sources over time can also be observed for the effects on income inequality. Future research is needed to grasp the effect on inequality in more detail assessing its determinants and causal relationships.
Keywords: 300; income inequality; poverty; rural development; Shapley decomposition; Tanzania